2006
DOI: 10.2341/05-54
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness in Ceramics with Different Finishing Techniques Using Atomic Force Microscope and Profilometer

Abstract: This study assessed the finishing and polishing of 3 ceramic materials: Vitadur Alpha, IPS Empress 2 and AllCeram. Surface modification techniques were selected to simulate dental practice. Forty-five specimens of each ceramic were divided into 5 groups of 9 specimens, which were finished using the following procedures: Group 1--glaze; Group 2--glaze, grinding and subsequent polishing with the Eve system; Group 3--glaze, grinding and subsequent polished with the Identoflex system; Group 4--glaze followed by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
21

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 25 publications
6
46
0
21
Order By: Relevance
“…Reglazing significantly reduces the surface roughness of ground and polished porcelain, as compared with polishing alone [4][5][6] . However, a number of studies have suggested that mechanical polishing of porcelain can produce equally smooth or smoother surfaces, as compared to glazing 7,8) . When a porcelain-veneered ceramic restoration having a flaw on the surface is placed in the mouth, moisture may hasten the breakdown of bonds between silica atoms over time through a process called slow crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…Reglazing significantly reduces the surface roughness of ground and polished porcelain, as compared with polishing alone [4][5][6] . However, a number of studies have suggested that mechanical polishing of porcelain can produce equally smooth or smoother surfaces, as compared to glazing 7,8) . When a porcelain-veneered ceramic restoration having a flaw on the surface is placed in the mouth, moisture may hasten the breakdown of bonds between silica atoms over time through a process called slow crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…Desta forma, estes fatores podem interferir significantemente na redução da rugosidade de superfície [3,11] . A resina composta Durafill, apresenta um menor tamanho de partícula se comparada a resina Master Fill, e desta forma, as suas médias de rugosidade variaram de acordo com o método de polimento empregado, sendo de 0,2 µm (TB) a 0,18 µm (PS); já para a resina Vênus, as médias variaram de 0,5 µm (FP) a 0,23 µm (TB).…”
Section: Alves L M M Et Al -Rugosidade E Microscopia De Força Atunclassified
“…Pode-se observar neste estudo, que as imagens foram importantes para representar os padrões de rugosidade obtidos para cada método de polimento e resina testada, ratificando a lisura na superfície das resinas [3] . É importante observar que os maiores valores de rugosidade representados por valores entre 0,7 e 1,44 µm pode facilitar o acúmulo de biofilme e contribuir para a instalação da doença periodontal [13] .…”
Section: Alves L M M Et Al -Rugosidade E Microscopia De Força Atunclassified
See 1 more Smart Citation
“…Alguns estudos sugerem que um bom polimento da superfície cerâmica com Discos Sof-lex ou Kit Shofu, por exemplo, produz menor rugosidade do que superfícies vitrificadas (Jacobi et al, 1991, Jagger;Harrison, 1994), o que corrobora com o presente estudo. Apesar da rugosidade clinicamente aceitável em cerâmicas ser de 0,2 µm (Tholt et al, 2006), alguns estudos in situ (Bollen et al, 1997) sugerem que esta rugosidade superficial (Ra) inicial seja ideal para a retenção bacteriana. Desta forma, o aumento na rugosidade superficial pode favorecer a formação e maturação do biofilme dentário Quirynen et al, 1990) resultando em maior risco de cárie e doença periodontal.…”
Section: Discussão Dos Resultadosunclassified